EFFECT OF ASSET STRUCTURE, PROFITABILITY, AND SALES GROWTH ON CAPITAL STRUCTURE OF MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE: PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Difi Dharmawan; Santi Susanti; Achmad Fauzi (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
This study examines the effect of asset structure, profitability, and sales growth on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The research method used is a descriptive quantitative method using secondary data with a sample of 48 manufacturing companies. The results of the requirements analysis test showed that the data were normally distributed and had a linear relationship. Based on the hypothesis test, it can be concluded that the asset structure, profitability, and sales growth have a significant positive effect on the capital structure (R2) is 18.1%. The conclusion that can be drawn in this study is that asset structure, profitability, and sales growth are factors that affect the capital structure, asset structure factors, profitability, and sales growth can be used by management in improving the company's capital structure and vice versa if shareholders want to predict capital structure when investing in a company. It is necessary to pay attention to the factors that affect the capital structure